2011
DOI: 10.4103/0974-1208.92287
|View full text |Cite
|
Sign up to set email alerts
|

A meta-analysis of the relationship between endometrial thickness and outcome of in vitro fertilization cycles

Abstract: OBJECTIVE:The objective was to evaluate the relationship between endometrial thickness on the day of human chorionic gonadotropin administration and pregnancy outcome in in vitro fertilization cycles.DESIGN:This was a systematic review and meta-analysis.MATERIALS AND METHODS:We identified 484 articles using Cochrane library, PubMed, Web of Science, and Embase searches with various key words including endometrial thickness, pregnancy, assisted reproductive technology, endometrial pattern, and in vitro fertiliza… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
39
0
2

Year Published

2013
2013
2017
2017

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 71 publications
(44 citation statements)
references
References 79 publications
3
39
0
2
Order By: Relevance
“…Bazal E 2 değerinin gebelik üzerine etkisinin anlamlı olmadığı ve üç yaş grubu karşılaştırıldığında da anlamlı bir değişim göstermediği kaydedilmiştir (Tablo 2). Yaşla birlikte hormonal değişiklikler endometrium fonksiyonlarını etkilemektedir; böylece endometriumun embriyonun implantasyonunu ve büyümesini destekleme yeteneği de azalmaktadır (22) . Endometrium kalınlığının gebeliğin oluşması ve implantasyon için önemli olduğu bilinmekle birlikte, IVF tedavisine alınan hastalardaki klinik önemi ile ilgili farklı görüşler bildirilmiştir.…”
Section: Discussionunclassified
“…Bazal E 2 değerinin gebelik üzerine etkisinin anlamlı olmadığı ve üç yaş grubu karşılaştırıldığında da anlamlı bir değişim göstermediği kaydedilmiştir (Tablo 2). Yaşla birlikte hormonal değişiklikler endometrium fonksiyonlarını etkilemektedir; böylece endometriumun embriyonun implantasyonunu ve büyümesini destekleme yeteneği de azalmaktadır (22) . Endometrium kalınlığının gebeliğin oluşması ve implantasyon için önemli olduğu bilinmekle birlikte, IVF tedavisine alınan hastalardaki klinik önemi ile ilgili farklı görüşler bildirilmiştir.…”
Section: Discussionunclassified
“…Previous studies have shown that the endometrium should be 8-14 mm thick for intrauterine implantation of zygotes (Aydin et al, 2013). Therefore, thin endometrium could result in repeated miscarriages or infertility, and in a decreased success rate of assisted reproduction (Momeni et al, 2011). The major features of thin endometrium are high uterine blood flow resistance and delayed growth of glandular epithelium, which could inhibit the expression of vascular endothelial growth factor (VEGF), thereby causing poor growth and development of blood vessels, reducing the perfusion of the endometrium (Miwa et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…The use of OCP pretreatment has also been associated with a reduction in endometrial thickness compared with no pretreatment, possibly due to the sustained suppression of luteinizing hormone (LH) and estradiol at the start of stimulation [13,14]. Although several studies have suggested a positive association between pregnancy rate and greater endometrial thickness on the day of ovulation trigger, up to a maximum of 12 to 14 mm [15], a reduced endometrial thickness at the start of the cycle may be beneficial in some patients to avoid overly thick endometrium following ovarian stimulation with human menopausal gonadotropin (hMG) [16].…”
Section: Introductionmentioning
confidence: 99%